Coffee farmer preferences for sustainable agricultural practices: Findings from discrete choice experiments in Vietnam. (15th September 2022) - Pham, Huong-Giang; Chuah, Swee-Hoon; Feeny, Simon
Abstract: Despite the proven benefits of sustainable agricultural practices (SAPs), adoption rates among farmers are still low, especially in developing countries. This paper seeks to assist policymakers devise approaches to encourage adoption by identifying the attributes of SAPs that can motivate Vietnamese coffee farmers to adopt them in production. Vietnam is the world's second largest coffee producer and the sector supports the livelihoods of over half a million people in the country. We conduct two different types of discrete choice experiments with over 300 Vietnamese coffee farmers to identify their SAP preferences. We analyse the data using cluster analysis and generalised multinomial logit models. The results are consistent across our different approaches. They show that these farmers have the strongest preferences for SAPs that can provide higher profits, lower risks (of output loss) and higher environmental benefits. These attributes received mean part-worth utilities of 0.251, 0.250 and 0.239 respectively. Attributes capturing the increase in daily operating efforts and time required to set up such practices are less important considerations. Further, the farmers are willing to pay on average between 26 and 32 million VND per hectare per year for a one level reduction in the risk of output loss and earn 15 million VND per hectare per year less in profits to achieve a one level increase in environmental benefits. Highlights: Two choice experiments are employed to access coffee farmer preferences for the sustainable practices in Vietnam. Coffee farmers are willing to accept practices that bring higher profits, lower risk and higher environmental benefits. Coffee farmers only care about daily effort and time required to set up when the change of coffee farming is a must.